1990
DOI: 10.1007/bf00228885
|View full text |Cite
|
Sign up to set email alerts
|

Development in the absence of spontaneous bioelectric activity results in increased stereotyped burst firing in cultures of dissociated cerebral cortex

Abstract: Quantitative analysis of neuronal firing patterns was used to study the effects of chronic suppression of bioelectric activity (BEA) on functional development in primary cultures of fetal rat cerebral cortex. BEA was monitored with extracellular electrodes in active control cultures or, after return to control medium, in cultures chronically silenced with tetrodotoxin (TTX) at around 7, 14, 21 and 42 days in vitro. Spike trains of single neurons lasting up to 25 min duration were analyzed using a previously pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 28 publications
7
61
0
Order By: Relevance
“…Previous studies of homeostatic plasticity have primarily followed the consequences of experimentally imposed disruptions of neuronal function. For example, genetic manipulation (Davis et al, 1997;Sandrock et al, 1997;Davis and Goodman, 1998;Guan et al, 2005), physical isolation of parts of the nervous system (Turrigiano et al, 1995;Thoby-Brisson and Simmers, 1998), pharmacological treatments (Berg and Hall, 1975;Ramakers et al, 1990;Turrigiano et al, 1998), or sensory deprivation during development (Desai et al, 2002). Only the scaling of synaptic inputs over the course of normal postnatal development shows a similar naturally occurring homeostatic plasticity (Desai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of homeostatic plasticity have primarily followed the consequences of experimentally imposed disruptions of neuronal function. For example, genetic manipulation (Davis et al, 1997;Sandrock et al, 1997;Davis and Goodman, 1998;Guan et al, 2005), physical isolation of parts of the nervous system (Turrigiano et al, 1995;Thoby-Brisson and Simmers, 1998), pharmacological treatments (Berg and Hall, 1975;Ramakers et al, 1990;Turrigiano et al, 1998), or sensory deprivation during development (Desai et al, 2002). Only the scaling of synaptic inputs over the course of normal postnatal development shows a similar naturally occurring homeostatic plasticity (Desai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, studies have shown spontaneous activity rates to be modifiable in response to chronic application of pharmacological agents (Ramakers et al, 1990;Turrigiano et al, 1998) or sensory deprivation (Maffei et al, 2004). However, it has not yet been established whether spontaneous activity can be regulated in vitro by altering levels of external activity presented in a physiological manner.…”
Section: Plasticity Of Spontaneous Activitymentioning
confidence: 97%
“…As mentioned above, plasticity in the levels of spontaneous activity in response to global pharmacological manipulations has been established (Ramakers et al, 1990;Rutherford et al, 1997;Turrigiano et al, 1998). However, it was not known whether levels of spontaneous activity are sensitive to manipulations that would mimic the synaptically driven activity observed in vivo.…”
Section: Plasticity Of Spontaneous Dynamicsmentioning
confidence: 99%
“…Over the past 20 years, physiologists repeatedly demonstrated that, like in vivo neurons (Kenet et al, 2003), cortical networks in vitro spontaneously synchronize once every 1-20 s (Fig. 1b,c), generating assembly activity events (Habets et al, 1987;Ramakers et al, 1990;Ramakers, 1991, 1992;Muramoto et al, 1993;Maeda et al, 1995Maeda et al, , 1998Kamioka et al, 1996;Nakanishi and Kukita, 1998;Ben-Ari, 2001;Corner et al, 2002;Marom and Shahaf, 2002;Plenz, 2003, 2004;Wagenaar et al, 2005Wagenaar et al, , 2006. Synchronizations with similar kinetics may also be evoked by site-specific electrical stimuli (Jimbo et al, 1999;Eytan et al, 2003).…”
Section: Dynamicsmentioning
confidence: 99%